An investigation into methods for capturing corporate knowledge in an Australian local government context - O'Donnell, Kye (Curtin University, 2007)
This research project investigates the processes of capturing corporate knowledge in an Australian local government context. The City of Perth, the capital city local government of Perth, Western Australia, is the organisation within which this study was conducted. A qualitative research methodology was utilised for this study in order to understand all the factors involved in knowledge sharing, including the human aspects. Data was collected exclusively through structured interviews consisting of a series of open questions. Digital transcripts of these interviews were produced and analysed by the researcher using qualitative data analysis software. The application of the research methodology has produced a rich set of results. The different types and sources of corporate knowledge used by participants and their views on knowledge capture processes are explored. Participants provide insight into their motivations in undertaking knowledge capture, the extent knowledge is shared in the organisation and barriers to sharing knowledge that they had encountered. The utilisation of the organisation’s information management processes and the overall purposes of knowledge capture were also explored by the study. Some of the results are quite predictable and generally supported by the literature, such as a preference for interpersonal communication in the sharing of knowledge. Other results are more unexpected including strongly expressed altruistic support for the good of the employing organisation as their motivation in supporting knowledge management activities and an understanding of the need for knowledge codification.